Training and Development of the Rank-and-File Employees among Select-ed Hotels in Cebu City - Polinar, Mark Anthony N.; Nardo, Gladys O.; Delantar, Alexander Franco A.; Buntiago, John Lemuel G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Employees constitute the definitive business resource for enhancing product quality and service excellence and consequently amplifying customer satisfaction. Without adequate training and development (T&D), employees would invariably be inept at unleashing their full potential. This study investigated the mechanisms employed in T&D programs for rank-and-file employees of several hotels in Cebu City. The study employed a quantitative method in a descriptive research design obtaining information from 71 respondents. Slovin's approach and convenience sampling were used. The weighted mean was employed in tabulation and quantification process. The findings revealed that respondents considered programmed instructions, job rotation, job simulation, role modeling, lectures, and team training to be very effective in the training programs. The authors concluded that these mechanisms if appropriately and situationally tweaked and rationalized, will result in more precise and targeted response to training issues leading to service excellence and customer satisfaction. A set of appropriate recommendations was drafted for possible use by establishments similarly situated